Pengaruh Komunikasi Internal terhadap Efektivitas Kerja Karyawan di Klinik Vavier Pondok Indah - Naila Fitri; Yohana Eva (Dinasti Review, 2025)
This study aims to determine the effect of internal communication on employee work effectiveness at Vavier Clinic, Pondok Indah. Effective internal communication is believed to be able to improve employee understanding, coordination, and involvement in achieving organizational goals. The research method used is a quantitative approach with a simple regression analysis technique. The research sample consisted of 30 employees with data collection through the distribution of closed questionnaires. The results of the analysis show that internal communication has a positive and significant effect on employee work effectiveness, especially in terms of productivity, quality of work results, and punctuality. This finding strengthens the theory and results of previous studies which state that internal communication is one of the key factors in creating an effective work environment. The implications of this study indicate the importance of management to strengthen the two-way communication system, information transparency, and increase employee involvement in the organizational communication process. This study recommends the development of communication strategy programs and interpersonal training to support work effectiveness in the clinic environment.